Dried blood spot in the genotyping, quantification and storage of HCV RNA: a systematic literature review. Issue 4 (4th November 2014) - Greenman, Jamie; Roberts, Teri; Cohn, Jennifer; Messac, Luke
Summary The entry of new all‐oral direct acting antiviral therapy for hepatitis C provides an opportunity to scale up HCV care in low‐ and middle‐income countries. In HIV, use of dried blood spots (DBS) has facilitated the diagnosis and management of HIV in resource‐poor settings. DBS may be used in a similar way to facilitate diagnosis and management of HCV. Here, we present a systematic review of the literature of DBS for HCV RNA detection and genotyping. Using an a priori review protocol, three databases were searched for studies published up to August 2013 that reported the use of dried blood and serum spots in genotyping, detection and measurement of HCV RNA, as well as the rate of degradation of HCV RNA when stored in DBS at room temperature. Nine papers were eligible for inclusion; eight studied DBS and one dried serum. Two studies measured concordance between genotype and subtype determined by DBS and whole plasma and both found 100% concordance. Four studies measured endpoint detection limits of HCV RNA‐positive samples by DBS and found positive predictive values of 100% down to 250, 334, 2500 and 24160 IU/mL. Two studies found deterioration of HCV RNA in DBS samples stored at room temperature, while two others failed to detect such deterioration. These results support the potential use of DBS for genotyping and HCV RNA detection. Studies of the use of DBS for HCV RNA viral load measurement and of the rate of degradation of HCV RNA when stored in DBS at ambient temperatures remain inconclusive.